2019
DOI: 10.1063/1.5114824
|View full text |Cite
|
Sign up to set email alerts
|

Dielectric response of electric-field distortions of the twist-bend nematic phase for LC dimers

Abstract: Wide band dielectric spectroscopy of bent-shaped achiral liquid-crystal dimers 1-n-bis(4cyanobiphenyl-4-yl) n-alkanes (CBnCB n=7,9,11) have been investigated in a frequency range 0.1 Hz to 100 MHz using planar-aligned cells of sample thicknesses ranging from 2 to 10 (m) over a temperature range that covers both nematic and twist bend nematic phases.Two peaks in the dielectric spectrum in the higher frequency range are assigned to the molecular relaxation processes. The peak at the highest frequency, ~ 40… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
9
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 10 publications
(9 citation statements)
references
References 69 publications
(82 reference statements)
0
9
0
Order By: Relevance
“…Thus IR absorbance components can, at least in principle, bring information about the ordering in the LC phase, via analyzing the order parameters S and D. In the nematic phase the order parameter, S, follows the Mayer -Saupe model well [39]. However, in the N TB phase, it has been demonstrated that the temperature dependence of the S-order parameter distinctly reverses its monotonic trend of increase to decrease at the transition temperature from the nematic (N) to the twist-band (N TB ) [26][27][28][29][30][31][40][41][42]. This is due to the rearrangement of molecules in the N TB phase as a helical structure appears.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Thus IR absorbance components can, at least in principle, bring information about the ordering in the LC phase, via analyzing the order parameters S and D. In the nematic phase the order parameter, S, follows the Mayer -Saupe model well [39]. However, in the N TB phase, it has been demonstrated that the temperature dependence of the S-order parameter distinctly reverses its monotonic trend of increase to decrease at the transition temperature from the nematic (N) to the twist-band (N TB ) [26][27][28][29][30][31][40][41][42]. This is due to the rearrangement of molecules in the N TB phase as a helical structure appears.…”
Section: Methodsmentioning
confidence: 99%
“…Such an exception, however, can indicate the possibility that the biaxial nematic phase might appear in between the nematic uniaxial (N U ) and the twist-bend (N TB ) phase [5,10]. A small sample biaxiality, which was found in N TB phase by comparing corresponding perpendicular absorbance components (in both alignment), A Y ≠A h , are likely to be induced by anchoring effect [39][40][41]. It seems, observation of true biaxiality is not possible without application of external field that can align secondary director.…”
Section: Physical Chemistry Chemical Physics Accepted Manuscriptmentioning
confidence: 99%
“…The experimental study of the structure of the N TB phase has mainly been carried out with nonresonant (SAXS, WAXS) [ 13 , 14 , 15 ] and resonant X-ray scattering [ 10 , 11 , 16 , 17 , 18 , 19 ], freeze–fracture transmission electron and atomic force microscopy (FFTEM, AFM) [ 8 , 9 , 20 , 21 , 22 ], polarized Raman [ 23 ], infrared [ 24 , 25 , 26 ], and nuclear magnetic resonance spectroscopy (NMR) [ 27 , 28 , 29 , 30 , 31 ], as well as with optical methods under applied electric fields [ 32 , 33 , 34 , 35 , 36 , 37 , 38 ] and magnetic fields [ 39 ]. The formation of the N TB structure has been modeled using rigid elements [ 15 , 40 , 41 ].…”
Section: Introductionmentioning
confidence: 99%
“…Finally, the X-ray evidence of the half-molecular length periodicity along the N TB helix led to a model based on the self-assembly of half-molecule-long blocks as the basic element of the N TB phase [ 10 , 18 , 42 ]. The N TB materials that have been most investigated are the cyanobiphenyl (CB)-based liquid crystal dimers (CBCnCB; n = 7, 9, 11) [ 8 , 9 , 10 , 11 , 13 , 16 , 21 , 23 , 27 , 28 , 29 , 30 , 31 , 32 , 33 , 36 , 37 , 38 , 39 ], where cyanobiphenyl units prefer an antiparallel arrangement due to dipole–dipole interactions, [ 43 , 44 , 45 , 46 ]. Up-to-date research has confirmed that molecular curvature is important for phase formation, but its stability increases as the bending angle decreases [ 47 , 48 , 49 , 50 , 51 , 52 ].…”
Section: Introductionmentioning
confidence: 99%
“…The soft materials, composed of highly anisotropic molecules, exhibit nearly limitless partially ordered mesophases. Bentshaped liquid crystals (LCs) [1,2], sometimes descriptively designated as LCs of banana-shaped molecules [3], can form one of these exotic phases, the twist-bend nematic (N TB ) phase [4][5][6][7][8][9][10][11][12][13][14][15][16][17]. In recent decades, considerable attention has been given to study the twist-bend nematic (N TB ) phase due to their novel mesostructure, chirality, and intriguing behavior such as elastic properties, which are strongly anisotropic and have an unusual temperature dependence .…”
Section: Introductionmentioning
confidence: 99%